Maternal parenting styles and exposure to community violence in influencing antisocial behavior with self-control as moderator among Penang Island adolescents in Malaysia - T'ng, Soo Ting (2013)
Empirical studies recognized parenting styles and exposure to community violence as correlates of antisocial behaviour. However, most studies only examined one of the correlates of antisocial behaviour at single time. The combination of both proximal (i.e.,role of the maternal parenting) and distal (i.e., exposure to violence) determinants are essential to generate wider understanding on the development of antisocial behaviour among adolescents. The present study aimed to examine the relationships between maternal parenting styles (authoritative, authoritarian, and permissive), exposure to community violence, and antisocial behaviour. This study also examined the role of selfcontrol as a moderator on the relationships between maternal parenting styles and antisocial behaviour, as well as exposure to community violence and antisocial behaviour. The present study applied correlational research design and Multi-Stage Cluster Random Sampling using Proportional Probability to Size (PPS) method to select 13 secondary schools from two Penang Island districts (Timur Laut and Barat Daya). A total of 1,149 respondents aged between 13- to 17-year old were included for final data analyses. Empirical data were collected through a self-administered questionnaire that constituted by four instruments (i.e., Parental Authority Questionnaire, Exposure to Community Violence scale, Brief Self-Control scale and Subtypes of Antisocial Behaviour). The present study successfully developed a full-fledged structural model,with adequate model fit at significance value p<.001, chi-square (χ2 =363.378),comparative fit-index (CFI) =.923, normed fit index (NFI) =.920, and root mean square error of approximation (RMSEA) =.073. The structural model indicated that the path loadings for the relationships between authoritative style and antisocial behaviour (β= –.21), authoritarian style and antisocial behaviour (β= –.08); permissive style and antisocial behaviour (β= .13); exposure to community violence and antisocial behaviour (β= .58) were found to be statistically significant, p<.05. The variance of antisocial behaviour was explained 40.1% by all the four predictors: authoritative style,authoritarian style, permissive style, and exposure to community violence. As for testing of moderation, the result revealed that the structural model did not show invariance across self-control groups (low self-control vs. high self-control) with Δχ2 =7.301, p<.05.The result showed that the relationship between exposure to community violence and antisocial behaviour was moderated negatively by self-control (z-score= –4.161, p<.05). However, self-control did not moderate the relationships between maternal parenting styles and antisocial behaviour. Findings from this study have significant implications. Theoretically, the findings may shed light on the role of maternal parenting styles and exposure to community violence on predicting adolescents‟ antisocial behaviour. From a practical perspective, the findings become a vital source for multiple targets such as parents, teachers, governmental and non-governmental organizations, to enhance their understanding and formulate effective prevention and intervention programs for antisocial adolescents.